PEMBENTUKAN KALUS BEBERAPA KULTIVAR TEBU (Saccharum officinarum L.) DENGAN KONSENTRASI 2.4 D BERBEDA - Susiyanti . (Jurnal Agroekoteknologi, 2010)
ABSTRACTSugarcane (Saccharum officinarum L.) is one of the most important crop in Indonesia. Improvement of sugarcane productivity mainly depend on quality of cultivar. Alternative method such as in vitro culture technique are needed to be uses to multiply clones of sugarcane. As the first step in many tissue culture experiment, it is necesssary to induce callus formation from the primary explantbefore regeneration to be plantlets. The objective of the study were to find the best callusing medium using several concentration of 2.4 D. The study was conducted using factorial design with Randomized Completely Design, with10 replicates. The first factor were: several culture 2.4 D media [kinetine 0.1mg l-1 + 2.4 D (1; 2; 3 dan 4 mg l-1)], and the second factor were sugarcane varieties (cv. Triton, cv. PSJT 94-41, and cv. PA 175). Data were analyzed by Duncan’s Multiple Range Test (DMRT) 5 %. Best callus induction from 3 clones of sugarcane was observed on medium containing 3 mg l-1 2.4 D. The optimum callusing medium for Triton cv, PSJT 94-41 cv. and PA 175 cv. respectively: 3,38; 3,79 and 2.85 mg l-1 mg l-1 2.4 D.Key words: sugarcane, callusing, 2.4 D, in vitro